Chronic cystoid macular oedema treated with intravitreal dobesilate. (9th July 2012) - Cuevas, Pedro; Outeiriño, Luis A; Angulo, Javier; Giménez-Gallego, Guillermo
Abstract : Dobesilate is an anti-inflammatory and antipermeability agent. Intravitreal administration of this compound is a therapeutically beneficial agent in the treatment of chronic cystoid macular oedema.